First-Principles Study of Dielectric Constant and Polarizability in Two Carbon Nanotubes - Sreepad, H. R. (Asian Journal of Science and Applied Technology, 2018)
First-principles calculations have been carried out on two Carbon Nanotubes having 54 and 72 carbon atoms. The Electronic density of state reveals that the materials show metallic nature. Dielectric constant has been computed in case of Carbon Nanotubes C54 and C72. The value of dielectric constant in Carbon Nanotube C54 comes out to be 7.06, 6.28 and 14.53 along X, Y and Z axes respectively and its average value comes out to be 9.29. Value of dielectric constant in Carbon Nanotube C72 comes out to be 167, 168 and 737 along X, Y and Z axes respectively and its average value comes out to be 357. Polarizability of Carbon Nanotube C54 has been estimated and it comes out to be 116(Å)3, 111(Å)3 and 142(Å)3 along X, Y and Z axis respectively. Polarizability in case of Carbon Nanotube C72 comes out to be 171(Å)3, 171(Å)3 and 173(Å)3 along X, Y and Z axes respectively.